Analisis Akad Pembiayaan Mudharabah pada Baitul Maal Wa Tamwil dalam Meningkatkan Pendapatan Masyarakat: Studi Kasus BMT UGT Sidogiri Cabang Tanggulangin - Fahri Huzeini; H. Hartoyo; Abdullah Faqih (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
This study aims to analyze the implementation of Mudharabah financing contracts at Baitul Maal Wa Tamwil (BMT) UGT Sidogiri Tanggulangin Branch and examine its role in increasing community income. The research background is based on the phenomenon of capital access difficulties experienced by micro and small entrepreneurs due to strict requirements and high interest burdens in conventional financial institutions. The research approach used is descriptive qualitative with data collection techniques through in-depth interviews, field observations, and documentation studies. Primary data sources were obtained from BMT managers, financing staff, and customers receiving Mudharabah financing, while secondary data came from contract documents, financial reports, and BMT profiles. Data analysis techniques using the Miles and Huberman model include data reduction, data presentation, and conclusion drawing. The research results show that the implementation of Mudharabah contracts at BMT UGT Sidogiri is in accordance with sharia principles and DSN-MUI Fatwa Number 07/DSN-MUI/IV/2000, with mechanisms that include the application stage, feasibility analysis using the 5C principles (Character, Capacity, Capital, Collateral, Condition), contract establishment with profit-sharing ratios based on mutual agreement, as well as disbursement and periodic supervision. Mudharabah financing has proven to have a significant impact on increasing community income, as demonstrated by increased business capital, productivity, and capital cost efficiency due to the absence of fixed interest burdens. Customers experienced increased business turnover and profit margins that could be allocated to improve family welfare. In addition, the presence of BMT has succeeded in reducing community dependence on loan sharks and contributing to local economic empowerment. The implications of this research indicate that the Mudharabah contract is an effective sharia financing instrument in promoting real sector development and financial inclusivity for micro-business actors.